AKTUALISASI NILAI-NILAI PANCASILA DALAM KEGIATAN P5 PADA KURIKULUM MERDEKA - Astuti, Asri Wiji; Putro, Ahmad Agung Yuwono (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
Education is an important aspect of personal growth and development. Education equips individuals with the knowledge, skills, and values necessary to live life. The lack of awareness and attention from families and society in implementing Pancasila values in everyday life causes students' low understanding and appreciation of Pancasila. In this case, there needs to be a collaborative effort between the government, schools, families and society through Pancasila Education value. The integration of the Pancasila Student Profile Strengthening Project (P5) activities in the Independent Curriculum is very important for holistic student development. This research aims to examine the Pancasila values contained in P5 activities in the Independent Curriculum. The type of research used is qualitative research using the literature review method. The data of this research were obtained from national articles/journals. The research data is in the form of descriptive data which is analyzed descriptively and provides an explanation of the results which is easy to understand. This research shows that the existing Pancasila values cover three domains, namely cognitive, affective and psychomotor.